Terpenoids identification and authenticity evaluation of longan, litchi and schefflera honey - Hequan Zhu; Yinan Du; Xun Lin; Zhonglian Huang; Jie Dong; Jiangtao Qiao; Hongcheng Zhang (Food Science and Human Wellness)
Terpenoids, as crucial plant secondary metabolites in honey, possess various bioactivities. This study aimed at investigating terpenoids of longan, litchi, and schefflera honey. Our results reveal that these three species of honey are characterized by abundant terpenoids, with eight terpenoids and one phenylpropanoid identified. Callunene, 3,4,5-trimethoxyphenylpropanal, schefflerin (4-2’-(3’,4’-dihydroxy-5’-methylfuran)-3,5,5-trimethyl-2-cyclohexenone) or abscisic acids may be as the characteristic components of longan, litchi, or schefflera honey. Abscisic acids were the most abundant components, average contents reached up to 53.67, 96.89 and 21.11 mg/kg, respectively, and the content ranges in three types of honey were 13.75−85.40, 19.93−177.31, 14.69−28.38 mg/kg, respectively. To our knowledge, the presence of schefflerin, (6R,9S)-vomifoliol, and 3,4,5-trimethoxyphenylpropanal in honey is a novel finding. We distinguish Thailand from Chinese mainland and Taiwan longan honeys, based on the ratio of abscisic acid and callunene content. Overall, our proposal to combine terpenoids with standard fingerprints seems to provide a novel and reliable solution for evaluating the authenticity of commercial honey.